Adoption and Impacts of Conservation Agriculture: Quasi Experimental Evidence from E. Africa - Bashaasha, Bernard; Laker-Ojok, Rita; Norton, Jay; Peck, Dannele; Owori, Moses (ResearchGate, 2013)
Conservation Agriculture is a recent and evolving concept to land management that seeks to optimise crop yields and farm profits in a manner that balances economic and environmental benefits. The underlying principles include avoiding soil tillage, maintaining soil cover and retaining crop residues, practicing crop rotations and improved fallows, precision placement of appropriate fertilisers, pesticides and herbicides (targeting of inputs), reliance upon integrated pest management (IPM) principles and avoidance of soil compaction, among others. We use binomial probit analysis and propensity score matching (PSM) methods to investigate the drivers of adoption and assess the impact of conservation agriculture among smallholder farmers in Eastern Uganda and Western Kenya. We use data from 800 small-holder farming households collected in 2010. The results show that the drivers of adoption are the same in both countries and that although both socioeconomic and biophysical characteristics drive the choice to use conservation agriculture practices, the latter appear to be more important than the former suggesting that increasing land degradation in East Africa will likely trigger increased adoption of conservation agriculture. Farmers whose main livelihood activity is either livestock or non-farm are less likely to adopt conservation agriculture practices whereas the relatively well off farmers are more likely to use conservation agriculture practices. Furthermore, results show that farmers in both countries are more likely to use conservation agriculture practices on degraded or soils prone to degradation. The results do not show any gender based differences. Using both Kernel and Nearest Neighbour Matching approaches, the results suggest significant impacts on maize yield of over 1000Kgs per ha on plots using conservation agriculture practices, negative impacts on the cost of inorganic fertilisers and result in labour savings of between 11–19 person days per ha per season. We conclude that conservation agriculture has a future in smallholder farming in east Africa with great potential to boost farm productivity and profitability through reduced use of both inorganic fertilisers and family labour inputs.
Keywords: Adoption; Conservation Agriculture; East Africa; Propensity Score Matching